Risk perception of the pre-distribution of stable iodine to guardians of children living around the Genkai Nuclear Power Plant, Saga Prefecture, Japan - Matsunaga, Hitomi; Orita, Makiko; Taira, Yasuyuki; Takamura, Noboru (PloS one, 2021)
Iodine thyroid blocking (ITB) is effective for preventing childhood thyroid cancer when radioactive iodine is released into the environment during a nuclear power plant accident. Japan employs the pre-distribution of stable iodine (PDSI) to residents living near nuclear power plants; however, the number of residents who have actually received stable iodine to date remains limited. The aim of this study was to evaluate the profile of guardians of children living around the Genkai Nuclear Power Plant (GNPP) in Japan. We distributed self-administered questionnaires regarding perception of risks associated with administration of stable iodide to approximated 400 guardians of children aged 0–6 in 10 kindergartens located in four municipalities. We obtained responses from 286 guardians, and after excluding invalid responses, 247 were included in the analysis. Logistic regression analysis revealed that living within 5 km of the GNPP (odds ratio [OR] = 4.48, 95% confidence interval [CI]: 2.43–8.24), awareness of preferential implementation of ITB to children (OR = 3.33, 95%CI: 1.78–6.22), and awareness of the prophylaxis booklet published by the local government (OR = 2.53, 95%CI: 1.37–4.68) were independently associated with PDSI for children. The main reasons for not receiving PDSI were “anxiety about the side effects of stable iodine” (40.2%), “distrust of the effectiveness of SI” (23.5%), “complicated procedures for receiving stable iodine” (15.7%) and “missed the date for receiving stable iodine” (8.8%). In the case of ITB implementation during a nuclear emergency, it is necessary to clarify the risk perceptions of guardians and adapt risk communication accordingly.